Zakat fitrah payers’ trust in Kelantan: mediation effects of disclosure practices, stakeholder management practices and customer satisfaction - Rufaidah Mat Nawi (2023)
The issue of zakat fitrah payers’ trust is rarely studied despite being associated with self-distribution practice, causing the zakat collection to never reach an optimum level. This self-distribution practice is the consequence of zakat fitrah payers losing confidence in zakat institutions due to certain governance factors. Since trust positively affects zakat compliance behavior and prohibits self-distribution practice, it is important to identify which governance factors can assist zakat institutions in gaining zakat fitrah payers’ trust. This study aims to test the effects of governance factors drawn from resource dependence and legitimacy theories namely state ownership, distribution quality, disclosure practices, council board, stakeholder management practices, service quality, and customer satisfaction on zakat fitrah payers' trust in Kelantan. This study also evaluates the mediation effects of disclosure practices and stakeholder management practices on the relationship between the council board and zakat fitrah payers’ trust. Besides, customer satisfaction as a mediator in the relationship between service quality and zakat fitrah payers’ trust was also measured. A total of 1,000 questionnaires were distributed to respondents from 10 districts in Kelantan. Out of 1000, 605 questionnaires were returned, and only 553 questionnaires were usable for further statistical analysis with a response rate of 55.3%. Five research objectives were developed with the first objective being to identify the level of zakat fitrah payers’ trust in Kelantan. An enhanced conceptual framework was developed to fulfill the other four objectives and 10 hypotheses were tested. The first research objective was analyzed by descriptive analysis (mean score value). Meanwhile, all hypotheses were tested by applying Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. Results showed that zakat fitrah payers’ trust is at a high level. Meanwhile, PLS-SEM results showed that distribution quality, council board, stakeholder management practices, and customer satisfaction affect zakat fitrah payers' trust positively. On the other hand, state ownership, disclosure practices, and service quality have an insignificant effect on zakat fitrah payers’ trust. Furthermore, this study also indicated that disclosure practices are not a mediator in the relationship between the council board and zakat fitrah payers' trust. However, stakeholder management practices play the role of complementary partial mediator in the relationship between the council board and zakat fitrah payers' trust. Customer satisfaction was also found to mediate the relationship between service quality and zakat fitrah payers' trust as a full mediator. This study adds nuance to the enhanced zakat payers' trust framework. This study is part of a growing body of research on zakat payers' trust from resource dependence and legitimacy theories' perspectives. This study will contribute to future research on topics related to gaining zakat payers' trust from governance and management perspectives.